Clinical studies using stem cells for treatment of retinal diseases: state of the art - Cotrim,Carina Costa (2020)
ABSTRACT Degenerative retinal diseases such as retinitis pigmentosa, Stargardt’s macular dystrophy, and age-related macular degeneration are characterized by irreversible loss of vision due to direct or indirect photoreceptor damage. No effective treatments exist, but stem cell studies have shown promising results. Our aim with this review was to describe the types of stem cells that are under study, their effects, and the main clinical trials involving them.